Forecasting short-run inflation volatility using futures prices: An empirical analysis from a value at risk perspective - Guillermo Benavides (Banco de México, 2010)
In this research paper ARCH-type models are applied in order to estimate the Value-at-Risk (VaR) of an inflation-index futures portfolio for several time-horizons. The empirical analysis is carried out for Mexican inflation-indexed futures traded at the Mexican Derivatives Exchange (MEXDER). To analyze the VaR with time horizons of more than one trading day bootstrapping simulations were applied. The results show that these models are relatively accurate for time horizons of one trading day. However, the volatility persistence of ARCH-type models is reflected with relatively high VaR estimates for longer time horizons. These results have implications for short-term inflation forecasts. By estimating confidence intervals in the VaR, it is possible to have certain confidence about the future range of inflation (or extreme inflation values) for a specified time horizon.
Keywords: C15; C22; C53; E31; E37; 330; bootstrapping; inflation; inflation-indexed futures; Mexico; Value at Risk; volatility persistence; Index-Futures; Inflation; Volatilität; Bootstrap-Verfahren; Risikomaß; Mexiko